THE INFLUENCE OF TOTAL QUALITY MANAGEMENT ON EMPLOYEE PERFORMANCE: A LITERATURE REVIEW STUDY - Purnama, Zuardiansyah Adi; Sar, Rela (LP2M IBK Nitro, 2025)
This study aims to analyze the influence of Total Quality Management (TQM) on employee performance through a systematic literature review. By collecting and analyzing 30 Scopus-indexed articles published between 2020 and 2025, the study identifies that the majority of the research (26 articles) reports a positive impact of TQM on employee performance, while a smaller portion (4 articles) presents insignificant or negative results. The key findings reveal that the effectiveness of TQM is strongly influenced by factors such as management commitment, organizational culture, technological integration, and transformational leadership. The Resource-Based View (RBV) theory predominates as the analytical framework, emphasizing that TQM can serve as a strategic resource that enhances productivity and competitive advantage. However, the implementation of TQM is not without challenges, including employee resistance and inadequate infrastructure readiness. This study provides practical implications for organizations seeking to optimize TQM in a holistic and contextual manner. It also offers recommendations for future research, particularly on integrating TQM with contemporary approaches such as green human resource management (green HRM) and digital transformation.